1999
DOI: 10.1103/physrevlett.82.374
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Armchair Carbon Nanotubes: Bosonization Approach

Abstract: The phase Hamiltonian of armchair carbon nanotubes at half filling and away from it is derived from the microscopic lattice model by taking the long-range Coulomb interaction into account. We investigate the low-energy properties of the system using the renormalization group method. At half filling, the ground state is a Mott insulator with a spin gap, in which bound states of electrons are formed at different atomic sublattices. [S0031-9007(98)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
105
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 20 publications
5
105
1
Order By: Relevance
“…A compelling correlated state of one-dimensional systems is the Luttinger liquid (LL) state. There is now abundant evidence from both theoretical [3,4,5,6,7] and experimental [8,9,10,11] side that the low energy properties of CNTs with a single shell, the single-wall carbon nanotubes (SWCNTs) can be described with the LL state. As a result, SWCNTs are regarded as a model system of the LL state, which could be exploited to further test the theories and novel experimental methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A compelling correlated state of one-dimensional systems is the Luttinger liquid (LL) state. There is now abundant evidence from both theoretical [3,4,5,6,7] and experimental [8,9,10,11] side that the low energy properties of CNTs with a single shell, the single-wall carbon nanotubes (SWCNTs) can be described with the LL state. As a result, SWCNTs are regarded as a model system of the LL state, which could be exploited to further test the theories and novel experimental methods.…”
mentioning
confidence: 99%
“…The DOS was ob-tained with a Green's function approach from the band structure that was calculated with a large k-point sampling. We considered the (9,9), (15,6), (10,10), (18,0), and (11,11) SWCNTs in order of increasing diameter. Here (n, m) denotes the lattice vectors on the graphene basis along which a cut-out stripe is folded up to represent a SWCNT [31].…”
mentioning
confidence: 99%
“…These parallel closely to the investigation of coupled Luttinger liquid chains. Their effect can be summarized as follows: at half filling, umklapp scattering generates a finite charge (Mott) gap in both the symmetric and antisymmetric charge sector, while spin backscattering leads to the opening of a spin gap in the spin sectors 3,4,5 . This is analogous to the spin ladder magnon excitations 14 found in the strong antiferromagnetic coupling limit.…”
mentioning
confidence: 99%
“…A compelling correlated state of one-dimensional systems is the Tomonaga-Luttinger liquid (TLL) state. The TLL state has been suggested to describe the low energy properties of CNTs with a single shell, the single-wall carbon nanotubes 2,3,4,5,6 . Transport 7 and photoemission studies 8,9 provided evidence for the existence of the TLL state in SWCNTs.…”
mentioning
confidence: 99%
“…9 From a theoretical point of view, it is well-known that the Luttinger liquid regime may break down in the carbon nanotubes, due to a variety of low-temperature instabilities. [10][11][12][13][14][15] When the effective phonon-mediated interactions are taken into account, it can be shown that the superconducting correlations may grow large upon suitable screening of the Coulomb interaction in the nanotubes. 16,17 This has raised the hopes that such correlations could be amplified by considering nanotube geometries with enhanced electron-phonon couplings.…”
Section: Introductionmentioning
confidence: 99%